Important Shark and Ray Areas can inform conservation planning in the Mediterranean and Black Seas - Rohner, Christoph A.; Richardson, Anthony J.; Garcia-Rodriguez, Emiliano; Charles, Ryan; Batlle-Morera, Amanda; Bortoluzzi, Jenny R.; Jabado, Rima W. (Cell Press, 2025)
The designation of protected areas needs to accelerate rapidly to achieve Target 3 of the Global Biodiversity Framework (GBF), raising concerns that protected area quality will be overlooked. Rather than basing systematic conservation planning primarily on species ranges, critical habitats for life history functions should be prioritized to enhance conservation outcomes. Such critical habitats are being identified as Important Areas, including Important Shark and Ray Areas (ISRA) for chondrichthyans. Solutions from systematic conservation planning scenarios with 73 chondrichthyan species in the Mediterranean and Black Seas greatly differed between approaches that ignore or include ISRAs. Including ISRAs led to higher costs for fisheries but protected a similar surface area (similar to 27% in both scenarios), while achieving better conservation outcomes. We highlight ways of reducing fishing costs while maintaining ISRA-based solutions. Systematic conservation planning using Important Areas gives decision makers a tool to balance cost with improved conservation quality, ultimately enhancing protected area network effectiveness by prioritizing critical habitats.
Keywords: Highlights; Marine organism; Nature conservation; Aquatic science; Zoology; Ichthyology